Potencial osteogênico in vivo de uma nova vitrocerâmica bioativa (Biosilicato®) - Granito, Renata Neves (2009)
Bioactive materials have the ability to bond and to integrate with bone tissue by forming a biologically active bonelike apatite layer, which has chemical and structural properties equivalent to the mineral phase of living bone. This process is determined by chemical reactions, whose products also influence the attachment, the proliferation, the differentiation and the mineralizing capacity of bone cells. Cellular responses contribute to the bioactive behavior, which is known for being higher in glass materials. However, as low mechanical properties are also inherent characteristics of glasses, researchers from Federal University of Sao Carlos were stimulated to develop nucleation and growth thermal treatments for the obtainment of the Biosilicate®, a fully-crystallized bioactive glassceramic of the quaternary system P2O5-Na2O-CaO-SiO2. Although a high in vitro osteogenic potential of this novel glass-ceramic has been previously demonstrated, its in vivo effects have not been investigated yet. To contribute to this knowledge, two studies were developed. The first one aimed to investigate the in vivo biological performance of Biosilicate® in bone defects of rat tibias, by means of hystomorphometric and biomechanical analyses 20 days after the surgical procedure. This study revealed that the fully-crystallized Biosilicate® has good bone-forming and bone-bonding properties. Hence, the second study aimed to compare the kinetics of the bone reactions to two different granulometric distributions of this novel glass-ceramic. Although they were both efficient for bone formation, smaller-sized particles of Biosilicate® showed partial reabsortion, which was accompanied by a more pronounced osteogenic activity within the period of time studied. Since positive results were obtained, the search for scaffolds that could serve as supports for the guided bone regeneration had started. A third study preliminarily evaluated cell culture and cocultures in porous structures made of Biosilicate® and of other chemical compositions that were specifically developed for this purpose. The findings suggest that, when in adjusted conditions, the scaffolds can create favorable cellular responses for bone tissue engineering purposes. Taken togheter, these studies point to a promising potential and provide directives for the use of Biosilicate® in bone regenerative processes.